(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
When designing houses in the southern regions of Ukraine there is a problem of protection of premises from direct solar radiation, which causes thermal and light discomfort. The practice of building construction in the southern areas shows that many houses are designed without taking into account the excess thermal action of insolation in the summer. In buildings with significant access of insolation to the premises, technical means of sun protection (air conditioning, internal cooling systems) are used, which leads to significant energy consumption. The rigidity of energy saving requirements leads to the need to develop new standards for the design and use of sun protection devices. They are able to significantly reduce the load on the cooling systems of buildings during the overheating period in summer and maintain or slightly reduce passive solar heating in winter. Due to the high brightness of sunlight and the appearance of glare on the mirror-reflecting surfaces, there is light (visual) discomfort. Sunscreens should be designed to provide protection against overheating in summer, reduce heat loss during the cold season, increase viewer comfort and visual contact with the environment. The norms set the minimum duration of insolation, but an excess of direct solar radiation can also lead to negative consequences. The practice of building construction in the southern areas shows that many houses are designed without taking into account the excess thermal action of insolation in the summer. In buildings with unlimited access of insolation to the premises, technical means of sun protection (air conditioning, internal cooling systems) are used, which leads to significant energy consumption. Currently in Ukraine there is no normative document that regulates the rules of design of sun protection devices, their types, requirements for them; basic efficiency criteria; methods of their determination. The peculiarity of the method is the use of a minimum amount of climatological information about the construction area. To perform calculations, it is enough to know: latitude, monthly average values of air temperature and its daily amplitude.